Nobility of Kazan province of the 2nd half of the 18th century: ranks’ makeup and the number of serfs owned - Alexander Feofanov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The study is based on the materials preserved in the Fund 1355 (Economic Notes to the plans of the General Land Survey of the Russian Empire) of the Russian State Archive of Ancient Acts (RGADA). These economic notes, compiled at the turn of the XVIII-XIX centuries, indicate the rank of landowner, and the number of souls according to the 5th revision. Service records (form lists) from the Fund 1349 of the Russian State Historical Archive (RGIA), years 1798-1802, had been used for the description of Kazan bureaucracy. At the end of the XVIII century, according to the 5th revision in the Kazan province, there were 1010 landowners, of which 465 were women. Most of the landowners were retired, this shows that the nobles actively used their right not to serve, granted to them by the Manifesto of 1762. Of those who served, a little more than half were in the state service, or served in garrisons, which they entered after active military (army or guards) service. Most of them retired in officer ranks. No more than 7.5 percent of nobles had general ranks of 1-5 classes. More than 20 percent of Kazan nobles owned at least a hundred souls, large landowners owning more than 500 souls compiled 5 percent. Many landowners (more than 19 percent) owned estates in other regions of the Russian Empire, most of all such estates were in the Nizhny Novgorod province. There were about 3 percent of titled nobles. The number of Kazan nobles educated at the Kazan gymnasium varies from 6 percent (in 1781) to 4 percent at the end of the 18th century. Moreover, this number of students of the Kazan gymnasium exceeds the total number of pupils of other educational institutions (primarily cadet corps). Median numbers show that nobles entered the service on average at the age of 14 (most - from 12 to 16), and received the first class rank at 21, more than half - from 18 to 24 years old. The vast majority of nobles entered military service, and then retired; a small part continued to serve in the civil service.